Effect of a short-term sodium chloride bath on juvenile pikeperch (Sander lucioperca) welfare - Krystyna Demska-Zakęś; Piotr Gomułka; Maciej Rożyński; Zdzisław Zakęś (Aquaculture Reports, 2021)
This study aimed to determine the impact of immersing pikeperch (body weight approximately 94 g) in an aqueous solution of sodium chloride on gasometric, hematological, and biochemical indicators. The impact of the sodium chloride concentration (NaCl 10, 15, and 20 g L−1), immersion time (30 or 60 min) and time of blood sampling (0 h – blood drawn immediately following fish immersion; 24 h – blood drawn one full day after manipulation) was analyzed. The immersion protocol did not bring significant stress for tested fish as none of the tested parameters was different when compared to results obtained in a blank control group. The immersion times tested impacted the gasometric indicators and blood acid-base balance (0 h). The levels of most of the whole blood and plasma biochemical indicators analyzed (Na+, Cl-, glucose, lactate, total protein, globulin) differed significantly in fish exposed to 15 g L−1 and 20 g L−1 of NaCl from those in the blank control group. These changes were short-term and after 24 h the values of these indicators did not differ from those confirmed in the control group. Significant increases in the levels of hemoglobin, hematocrit, and red blood cells were confirmed in groups 10 g NaCl L−1/30 min/0 h and 20 g NaCl L−1/30 min/0 h and these changes persisted 24 h following immersion. Significant increases in the number of white blood cells (0 h) were confirmed in all groups, and this persisted for 24 h following immersion. The current study revealed transient, dose- and time-dependent stress reactions in pikeperch subjected to abrupt changes in water salinity and indicated that this species has significant recovery abilities in response to salinity shifts of short duration.